Delayed Intracerebral Hemorrhage Secondary to Ventriculoperitoneal Shunt: A Case Report and Literature Review. Issue 47 (November 2015) - Ma, Li; Chen, Yi-Li; Yang, Shu-Xu; Wang, Yi-Rong
Abstract : Abstract: The ventriculoperitoneal (VP) shunt is a routine procedure for cerebrospinal fluid (CSF) diversion, and is associated with many complications. A delayed hemorrhage after the VP shunt surgery, however, is quite rare. In this study, we report a case involving late-onset hemorrhage. The 67-year-old male patient with a history of head trauma and brain surgery underwent a VP shunt placement for hydrocephalus. The surgery course was uneventful and no bleeding was revealed in the first computed tomographic (CT) scan after the procedure. However, a massive intraparenchymal and intraventricular hemorrhage occurred 8 h following adjustment of the valve system on the 8th day after surgery. Erosion of the vasculature by catheter cannulation and a sudden reduction of CSF pressure after downregulation of the valve could be one of the possible causes of the intracerebral hemorrhage (ICH).